Çorum Şer’iyye sicilleri çerçevesinde aile hukuku davaları (1255-1290/ 1840-1874) - Yavaş, Ferhan Sultan (My University, 2016)
Osmanlı hukuk sistemi İslam hukuku ve özelde Hanefi ekolü uygulamalarıyla öne çıkmıştır. Bu uygulamalar dikkatli bir biçimde kayıt altına alınmıştır. Çalışmamızda bir Anadolu kenti olan Çorum’un 19. yy. Şer’iyye sicilleri temel alınarak İslam aile hukuku bakımından incelemesi yapılmıştır. Bir anlamda teorideki İslam hukukunun pratikte nasıl hayat bulduğu tespit edilmiştir. Temel kaynak olarak 1255-1290/ 1840-1874 yılları arası Çorum Şer’iyye Sicilleri ve fıkıh eserleri kullanılmıştır. Öncelikle siciller birkaç yönden tanıtılarak önemi vurgulanmış, davalar sınırlar dâhilinde konularına göre tasnif edilmiş ve Osmanlı toplumunda ve hususiyetle Çorum ölçeğinde İslam hukukuna bağlı kalınan noktalar ile farklı uygulamalar tespit edilmeye çalışılmıştır. yye, Sicil, Çorum, Aile Hukuku Faculty / School / Vocational School :Institute of Social Sciences Department :Basic Islamic Sciences Programme :Islamic Law Supervisor :Associate Professorİsmail Cebeci Degree Awarded and Date :Master/ June, 2016 Shariyyah, register, Çorum, family law

Ottoman Law System became prominent with shariah (Islamic law) and dedicatedly with implementation of Hanafi school. These implementations was recorded attentively. In this study, Çorum, a city of Anatolia was examined in terms of Islamic family law based on 19. century's court records. In a sense Islamic law in theory was compared with Islamic Law in practice. As a main source, 1255-1290/ 1840-1874 years' Çorum Court Records and works of Islamic jurisprudence were used. Court records were introduced in some aspects and the importance of court records was emphasized, cases were classified according to the subjects within the limits. Additionally, this study focuses on the points which is connected to Islamic law and different implementations in Ottoman society especially in the scale of Çorum. Shariyyah, register, Çorum, family law
Keywords: Hukuk; İslam dini